INTERPRETASI SIMBOLIK APAY SEBAGAI PROSES INISIASI MASYARAKAT TUBABA MELALUI PERTUNJUKAN TIKEW: CIRCLE OF LIFE - Zefanya, Arsya Putri; Isa Ansari, Isa Ansari (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
Tikew is one of plants that gorws on swampy areas, in Tulang Bawang Barat, Tiyuh Gedung Ratu. One of the products made form Tikew is Apay, which is part of the local wisdom of the Tubaba community and is used in daily life. The implementation of Apay as an initiation maker of daily life in the Tubaba community is directly related to the philosophy they call "Hidup Tikew Mati Tikew". This research aims to explain the symbolic interpretation of Apay as an initiation process in the lives of Tubaba community through the performance art titled of "Tikew: Circle of Life". This leads to several research questions; Why Tikew considered to philosophy of Tubaba's community life that is implemented through Apay? How is Tikew and Apay implemented as symbols in the performance art? And, what is the relationship between Apay and the performance in the initiation process of Tubaba community's life?. The research method employed is descriptive qualitative, who aims to participant observation and interviews. The approach underlying this research is the Symbolic Interpretivism Theory of Clifford Geertz. The finding of this study reveal the symbolic meaning of Apay as a marker of social change and as an initiatory sign of the life processes of the Tubaba community.